Penerapan Model Problem Based Learning (PBL) dan Permainan Board Question untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas IV SD Negeri Purwantoro 1 Kota Malang - Rosidah, Vivin Khoirir; Ekowati, Dyah Worowirastri; Astutik, Pipit Pudji (Jurnal Simki Pedagogia, 2023)
The purpose of this study was to determine the increase in learning outcomes by applying the PBL Model and board question games to the science learning outcomes of class IV students at SDN Purwantoro 1 Malang city in the 2022/2023 academic year. In this case the research that will be carried out is research using the Classroom Action Research (PTK) method, the research that will be carried out will involve students who are in class while carrying out learning or can be called Classroom Action Research. the application of the PBL Model and Game Board Questions to fourth grade students at SD Negri Purwantoro 1 City of Malang can improve student learning outcomes, it can be seen from the data taken by the researchers showing that there was an increase from cycle I student learning outcomes reached 60.71%, but after the action was taken there was an increase in student learning outcomes to 89.28% this figure showed that it had reached 75% of the desired minimum target category.